2021
DOI: 10.1002/cac2.12117
|View full text |Cite
|
Sign up to set email alerts
|

The EGFR‐P38 MAPK axis up‐regulates PD‐L1 through miR‐675‐5p and down‐regulates HLA‐ABC via hexokinase‐2 in hepatocellular carcinoma cells

Abstract: BackgroundImmunotherapy has been shown to be a promising strategy against human cancers. A better understanding of the immune regulation in hepatocellular carcinoma (HCC) could help the development of immunotherapy against HCC. The epidermal growth factor receptor (EGFR) signaling is frequently activated in HCC and plays important roles in tumorigenesis. However, its role in HCC immunity is still largely unknown. This study aimed to investigate the impact of EGFR signaling on programmed death‐ligand 1 (PD‐L1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Similarly, VersicanV1 was also found to enhance EGFR-PI3K-Akt signalling pathway in HCC cells [44]. A recent study by Liu et al [45] demonstrated that, in HCC cells, the EGFR-P38 MAPK axis may up-regulate PD-L1 via miR-675-5p and down-regulate HLA-ABC via HK2 and this might be responsible for the immune suppression in HCC, and they suggest that EGFR signalling might be targeted for HCC immunotherapy. Hence, based on the potential role of EGFR in HCC and also key network hub status in the current study, the phytocompounds were screened against EGFR.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, VersicanV1 was also found to enhance EGFR-PI3K-Akt signalling pathway in HCC cells [44]. A recent study by Liu et al [45] demonstrated that, in HCC cells, the EGFR-P38 MAPK axis may up-regulate PD-L1 via miR-675-5p and down-regulate HLA-ABC via HK2 and this might be responsible for the immune suppression in HCC, and they suggest that EGFR signalling might be targeted for HCC immunotherapy. Hence, based on the potential role of EGFR in HCC and also key network hub status in the current study, the phytocompounds were screened against EGFR.…”
Section: Discussionmentioning
confidence: 86%
“…PD-L1 upregulation in HCC cells can be driven also by the EGFR-P38 MAPK axis, via miR-675-5p [ 73 ]. Interestingly, phospho-EGFR directly correlated with PD-L1 expression and inversely correlated with HLA-ABC in HCC tissues and cell lines.…”
Section: Micrornas Directly Targeting Pd-l1mentioning
confidence: 99%
“…PD-L1 inhibition T-cell function and the activation of EGFR by its ligand can induce the positive regulation of this molecule. In this sense, it has been suggested that the EGFR inhibitor Gefitinib was able to decrease PD-L1 expression and inhibition of T-cell-mediated lysis of liver cancer cells through EGFR activation [ 45 ]. Thus, anti-PD-L1 antibody therapy could be used to decrease immunosuppression in cancer patients with uncontrolled EGFR activation [ 46 ].…”
Section: The P38 Mapk Pathwaymentioning
confidence: 99%
“…In addition, the expression levels of miR-675-5p differ in different cancers contributing to several functions such as cell proliferation and invasion, as well as metastasis [ 47 , 48 ]; the downregulation of miR-675-5 by p38 MAPK activation provides stability to the PD-L1 RNA through the 3’-UTR region and thus causes PD-L1 accumulation. For this reason, the EGFR/p38 MAPK axis has been involved in the regulation of PD-L1 through miR-675-5p with interesting potential on the immunotherapy of hepatocellular carcinoma that needs more in-depth studies [ 45 ].…”
Section: The P38 Mapk Pathwaymentioning
confidence: 99%